2010
DOI: 10.4104/pcrj.2010.00034
|View full text |Cite
|
Sign up to set email alerts
|

COPD prevalence and the differences between newly and previously diagnosed COPD patients in a spirometry program

Abstract: Aims: To evaluate the prevalence and severity of COPD in a primary care population participating in a spirometry program. Differences between newly and previously diagnosed COPD patients were identified.Methods: A spirometry program was conducted in 15 primary care centres. Visitors aged over 30 years who were willing to perform spirometry were included in this program.Results: A total of 1,526 subjects provided acceptable spirometries. COPD prevalence in our population was 18.4%, of whom 69.0% were newly diag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
56
3
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 54 publications
(77 citation statements)
references
References 49 publications
15
56
3
3
Order By: Relevance
“…A number of studies have shown that COPD has been more prevalent among smokers, older adults and males in Greece [31][32][33]35]. COPD patients have displayed this profile both pre-crisis and throughout the crisis period.…”
Section: Profile Of Copd Patients In Greece During the Crisismentioning
confidence: 99%
See 4 more Smart Citations
“…A number of studies have shown that COPD has been more prevalent among smokers, older adults and males in Greece [31][32][33]35]. COPD patients have displayed this profile both pre-crisis and throughout the crisis period.…”
Section: Profile Of Copd Patients In Greece During the Crisismentioning
confidence: 99%
“…There is a linear increase in COPD prevalence with patients age [25,[31][32][33]. The average age of COPD patients across studies was 71 and 68 years for the pre- [33] and post-crisis period [35], respectively. Comparably, global estimates have reported that 40% of patients are aged 40-60 years and 30% are aged >60 years [25].…”
Section: Profile Of Copd Patients In Greece During the Crisismentioning
confidence: 99%
See 3 more Smart Citations